PERAN PENTING KOMUNIKASI MANAJEMEN DALAM PENDIDIKAN - Ayu Larasati; Tirton Nefianto (Institut Penelitian Dan Pengambangan Mandalika Indonesia (IP2MI), 2022)
Communication is a process by which a person or group, organization, and society create, and use information to connect with the environment and people other. Management is often also defined as the art of carrying out a jobthrough other people. Therefore communication management is a combination of communication concepts and management applied in various communication activities with the aim tomake the implementation of the communication run effectively, so that the message or the expected result from the withdrawal of the information was as expected. Communication Management consists of two words, namely Management and communication. In the process of implementing managementnwork through its functions, namely planning, organizing, controlling and lead various efforts in achieving goals. Communication management was born because of the demand to bridge between communication theorists and communication practitioners. The role of communication in education management is communication as a source of educational information, communication as controller and coordination, communication as planning and achieving goals, and communication as an effort to increase motivation.